2017
DOI: 10.1051/0004-6361/201630049
|View full text |Cite
|
Sign up to set email alerts
|

Glycolaldehyde in Perseus young solar analogs

Abstract: Context. The earliest evolutionary stages of low-mass protostars are characterised by the so-called hot-corino stage, when the newly born star heats the surrounding material and enrich the gas chemically. Studying this evolutionary phase of solar protostars may help understand the evolution of prebiotic complex molecules in the development of planetary systems. Aims. In this paper we focus on the occurrence of glycolaldehyde (HCOCH 2 OH) in young solar analogs by performing the first homogeneous and unbiased s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 37 publications
2
63
0
Order By: Relevance
“…A previous analysis of the HDO lines detected in the ASAI observations revealed the presence of a hot ( 150 K), dense ( 3 × 10 7 cm −3 ) and compact (∼ 25 au) region, which could indicate the presence of a hot corino (Codella et al 2016). The actual confirmation of the hot corino arrived soon after with the detection of glycolaldehyde (HCOCH2OH), which emits over a ∼ 70 au diameter region centered on SVS13-A (De Simone et al 2017). Subsequent higher spatial resolution observations by Lefèvre et al (2017) found that VLA4A is associated with compact continuum emission, suggestive of a disk smaller than about 50 au.…”
Section: Source Backgroundmentioning
confidence: 92%
“…A previous analysis of the HDO lines detected in the ASAI observations revealed the presence of a hot ( 150 K), dense ( 3 × 10 7 cm −3 ) and compact (∼ 25 au) region, which could indicate the presence of a hot corino (Codella et al 2016). The actual confirmation of the hot corino arrived soon after with the detection of glycolaldehyde (HCOCH2OH), which emits over a ∼ 70 au diameter region centered on SVS13-A (De Simone et al 2017). Subsequent higher spatial resolution observations by Lefèvre et al (2017) found that VLA4A is associated with compact continuum emission, suggestive of a disk smaller than about 50 au.…”
Section: Source Backgroundmentioning
confidence: 92%
“…Interestingly, complex organic molecules (COMs) from the hot corino of SVS13A (e.g. López-Sepulcre et al 2015;De Simone et al 2017) peak on or close to VLA4A (see Fig. 2 and Belloche et al, in prep.…”
Section: Dust and Com Distribution In Svs 13amentioning
confidence: 97%
“…Codella et al (2014) found a knotty jet driven by Per-emb-27 with a dynamical time of < 30 − 90 yr, which is considered to be a signature of episodic accretion (Vorobyov et al 2018). Per-emb-44 contains also a central hot region with a detection of glycolaldehyde (De Simone et al 2017;Bianchi et al 2019). Multiple components are found in continuum observations by Tobin et al (2016Tobin et al ( , 2018, including a close binary with a separation of 0.…”
Section: Dependence Of the Physical And Chemical Modelsmentioning
confidence: 99%